ANALYSIS OF LEGAL SUPERVISION IN PREVENTING CRIMINAL PRACTICES AND CAPITAL MARKET VIOLATIONS - Wandi Subroto (AKSELERASI: Jurnal Ilmiah Nasional, 2021)
This study aims to analyze legal supervision in preventing criminal practices and capital market violations. The type of research used in this study is the juridical-normative method, namely research on a legal principle contained in positive law that has been applied in Indonesia. The positive law in question is the regulation that regulates Capital Market Number 8 of 1995, the Law on the Financial Services Authority, and other Implementing Regulations. The types of legal sources used in this study are secondary legal sources and tertiary legal sources collected using the library research method. The research analysis used qualitative methods which were analyzed using a sociological approach. Qualification of forms of criminal acts Law no. 8/1995 concerning the Capital Market is regulated in Article 103 paragraph (1), Article 104, Article 106 and Article 107. As for criminal acts in the form of violations, it is regulated in Article 103 paragraph (2), Article 105 and Article 109. The forms of sanctions for violations are divided into: administrative sanctions, civil sanctions, and criminal sanctions.